Ecofeminist Movement in Islamic Women’s Activism: The Case of ‘Aisyiyah - Zahra Zayyina Hanifah; Muhammad Wahid Nur Tualeka; Mahmud Muhsinin; Soumia (Pusat Studi Gender dan Anak, 2026)
The growing environmental crisis has intensified scholarly interest in ecofeminism as an approach that integrates ecological sustainability, gender justice, and religious values. However, empirical evidence on how ecofeminist values are institutionalized within Islamic women's organizations remains limited. This study examines how ecofeminism is institutionalized within the Environment and Disaster Management Unit (LLHPB) of the East Java Regional Board of 'Aisyiyah by exploring the interaction between religious values, organizational structures, and women's ecological consciousness in shaping environmental practices. A qualitative case study approach was employed. Data was collected through in-depth interviews, participant observation, organizational documents, and institutional publications and analyzed using the Miles and Huberman interactive model. Guided by Islamic Ecofeminism and Pierre Bourdieu's Theory of Habitus, the findings show that ecofeminist values are institutionalized through three interrelated mechanisms: participatory leadership, the integration of da'wah bil-hal with environmental education and disaster mitigation, and the development of an ecological habitus through cadre formation and community engagement. These mechanisms collectively give rise to a Habitus-Based Religious Ecofeminism Model, illustrating how Islamic values are translated into sustainable environmental practices through organizational processes. This study contributes to the literature by advancing an institutional perspective on Islamic ecofeminism and demonstrates how faith-based women's organizations promote ecological sustainability through the integration of religion, gender, and environmental action.